Improvement of business performance in small-medium enterprise (SME) : Evidence from a sanitaryware company in Malaysia - Norwazli, Abdul Wahab; Low, Yong Hong (Universiti Malaysia Pahang, 2023)
The market for sanitaryware in the world was estimated at USD 13.00 billion in 2021, and it is anticipated to expand at a compound annual growth rate (CAGR) of 5.1% over the next five years. Sanitaryware includes items like washbasins, pedestals, and other sanitary equipment like toilets. Typically, ceramic, pressed metal, and other materials are used to create these products. One of the key factors fuelling the market's expansion globally is the growing awareness of superior sanitaryware items due to different benefits to cleanliness and health. This paper uses the Fishbone diagram technique to identify the potential root causes of fluctuating revenue of a sanitaryware retailer in Malaysia. As a result, the proposed solutions to improve the business performance of the company are proposed using the Business Excellence Model approach. The findings of this research are expected to make important contributions to the sanitaryware industry as it will help the companies to understand the customer behaviours and strategies to improve their business performance. This research also can act as a basic guideline when they want to analyse their business performance using Fishbone diagram method